The Importance of Storytelling in Teaching Vocabulary to Elementary Students - Gulchеxrаxоn Tilаvоldiyеvа (Journal of Innovation in Education and Social Research, 2024)
In this article, the opinions of our country's and foreign scientists are mentioned about the importance of storytelling in teaching vocabulary to elementary school students.